2020
DOI: 10.1186/s12970-020-00357-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-ingredient pre-workout supplementation changes energy system contribution and improves performance during high-intensity intermittent exercise in physically active individuals: a double-blind and placebo controlled study

Abstract: Background: Nutritional ergogenic aids are commonly used to boost physiological adaptations to exercise and promote greater fitness gains. However, there is a paucity of data about multi-ingredient pre-workout supplementation (MIPS). Therefore, the aim of the present study was to investigate the acute effects of MIPS on the oxidative, glycolytic and ATP-CP energy systems contribution, time spent above 90% VO 2max (T90% VO 2max ), excess post-exercise oxygen consumption (EPOC) magnitude, number of efforts and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Sports performance improvements were probably due to reduced muscle damage [52,53] and stimulation of anabolic hormone [51] action attributable to the MIPS' content. MIPS supplementation appears to be effective in increasing the energy contribution on aerobic and anaerobic metabolism and increasing energy expenditure would increase the time to exhaustion [54]. In addition, ingestion of ingested MIPS would allow cyclists to endure higher plasma lactate levels and for longer periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Sports performance improvements were probably due to reduced muscle damage [52,53] and stimulation of anabolic hormone [51] action attributable to the MIPS' content. MIPS supplementation appears to be effective in increasing the energy contribution on aerobic and anaerobic metabolism and increasing energy expenditure would increase the time to exhaustion [54]. In addition, ingestion of ingested MIPS would allow cyclists to endure higher plasma lactate levels and for longer periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…PWS consumption in recreationally or physically trained males leads to many performance-enhancing benefits, including improvements in mean power output during single and repeated sprints [ 15 , 16 ], agility, reaction times, lower body muscular endurance and reduced fatigue [ 17 , 18 ]. PWS ingestion also improves anaerobic performance [ 19 ] and prolongs time to exhaustion during high-intensity intermittent exercise [ 20 ]. In addition, PWSs seem to increase the capacity for greater training volumes, muscular endurance, and power performance throughout a training session [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Martinez et al [ 33 ] showed significant increases in peak and mean power in Wingate anaerobic test following consumption of MIPS. In a study by Figueiredo et al [ 34 ], acute MIPS consumption was effective at increasing aerobic and anaerobic alactic energy contribution and time to exhaustion. In other studies, no effect of acute MIPS consumption was found on Wingate anaerobic cycling performance [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literature and qualitative studies examining the effectiveness of MIPS supplementation are only preliminary [ 6 ], and previously published papers reported contradictory data [ 33 36 ]. Ingestion of the pre-workout dietary supplement led to significant improvements in anaerobic peak and mean power values measured in Wingate test in recreationally trained males [ 33 ], and was effective at increasing both aerobic and anaerobic alactic energy contribution and time to exhaustion during a high-intensity interval exercise in physically active individuals [ 34 ]. Another studies [ 35 , 36 ] found no effect of MIPS on on muscular endurance and Wingate anaerobic capacity sprint performance in recreationally active participants or strength/power athletes.…”
Section: Introductionmentioning
confidence: 99%